Plant non-coding RNAs function in pollen development and male sterility - Nie, Hushuai; Cheng, Cheng; Kong, Jie; Li, Huijing; Hua, Jinping (Frontiers in Plant Science, 2023)
Male sterility is classified as either cytoplasmic male sterility (CMS) or genic male sterility (GMS). Generally, CMS involves mitochondrial genomes interacting with the nuclear genome, while GMS is caused by nuclear genes alone. Male sterility is regulated by multilevel mechanisms in which non-coding RNAs (ncRNAs), including microRNAs (miRNAs), long non-coding RNAs (lncRNAs), and phased small interfering RNAs (phasiRNAs), which have been proven to be critical elements. The development of high-throughput sequencing technology offers new opportunities to evaluate the genetic mechanism of ncRNAs in plant male sterility. In this review, we summarize the critical ncRNAs that regulate gene expression in ways dependent on or independent of hormones, which involve the differentiation of the stamen primordia, degradation of the tapetum, formation of microspores, and the release of pollen. In addition, the key mechanisms of the miRNA–lncRNA–mRNA interaction networks mediating male sterility in plants are elaborated. We present a different perspective on exploring the ncRNA-mediated regulatory pathways that control CMS in plants and create male-sterile lines through hormones or genome editing. A refined understanding of the ncRNA regulatory mechanisms in plant male sterility for the development of new sterile lines would be conducive to improve hybridization breeding.